Graphitic carbon nitride (g‐C3N4)‐based nanosized heteroarrays: Promising materials for photoelectrochemical water splitting. Issue 2 (21st May 2020) - Wang, Liqun; Si, Wenping; Tong, Yueyu; Hou, Feng; Pergolesi, Daniele; Hou, Jungang; Lippert, Thomas; Dou, Shi Xue; Liang, Ji
Abstract: Photoelectrochemical (PEC) water splitting is recognized as a sustainable strategy for hydrogen generation due to its abundant hydrogen source, utilization of inexhaustible solar energy, high‐purity product, and environment‐friendly process. To actualize a practical PEC water splitting, it is paramount to develop efficient, stable, safe, and low‐cost photoelectrode materials. Recently, graphitic carbon nitride (g‐C3 N4 ) has aroused a great interest in the new generation photoelectrode materials because of its unique features, such as suitable band structure for water splitting, a certain range of visible light absorption, nontoxicity, and good stability. Some inherent defects of g‐C3 N4, however, seriously impair further improvement on PEC performance, including low electronic conductivity, high recombination rate of photogenerated charges, and limited visible light absorption at long wavelength range. Construction of g‐C3 N4 ‐based nanosized heteroarrays as photoelectrodes has been regarded as a promising strategy to circumvent these inherent limitations and achieve the high‐performance PEC water splitting due to the accelerated exciton separation and the reduced combination of photogenerated electrons/holes. Herein, we summarize in detail the latest progress of g‐C3 N4 ‐based nanosized heteroarrays in PEC water‐splitting photoelectrodes. Firstly, the unique advantages of this type of photoelectrodes, including the highly ordered nanoarray architectures and the heterojunctions, are highlighted. Then, different g‐C3 N4 ‐based nanosized heteroarrays are comprehensively discussed, in terms of their fabrication methods, PEC capacities, and mechanisms, etc. To conclude, the key challenges and possible solutions for future development on g‐C3 N4 ‐based nanosized heteroarray photoelectrodes are discussed. Abstract : Constructing graphitic carbon nitride (g‐C3 N4 )‐based heteroarrays as photoelectrodes has been regarded as the most straightforward and efficient strategy for enhancing the photoelectrochemical (PEC) performance of g‐C3 N4 . On the one hand, heterojunctions between g‐C3 N4 and the secondary material can accelerate the separation of photogenerated electrons/holes. On the other hand, highly‐ordered array architectures provide the fast transport routes for photogenerated carriers, thus significantly suppressing the recombination of photo‐induced charges. Briefly, g‐C3 N4 ‐based heteroarrays will play a key role in the next years, and will help to pave an avenue to achieve the efficient and stable PEC water splitting for sustainable solar‐driven hydrogen production.